The World in Eleven Dimensions Supergravity, supermembranes and M-theory - Duff, M.J (Taylor & Francis, 1999)
A unified theory embracing all physical phenomena is a major goal of theoretical physics. In the early 1980s, many physicists looked to eleven-dimensional supergravity in the hope that it might provide that elusive superunified theory. In 1984 supergravity was knocked off its pedestal by ten-dimensional superstrings, one-dimensional objects whose v